Using ICTs to Promote EFL Third Graders’ Engagement (2024)
ABSTRACT: This action research carried out at Institución Educativa Sor Juana Inés de la Cruz in Medellín sought to determine how content presented through ICTs fostered EFL children’s engagement. Different types of audio, visual, audiovisual materials, and games were used in order to observe students’ engagement forms and changes. Within an action research framework, data collection instruments used for this qualitative study were one pre- and one post- LIKERT student surveys, four class video recordings, cooperating teacher and advisor reports, pre-service teacher journal entries, student artifacts, and one student interview at the end of the action plan. The analysis of the data revealed that the use of ICTs fostered students’ vocabulary learning and retention, their progressive desire to participate in spoken form, and their time on task effectiveness. Teacher mediation and planning were key to the learning of students.